Evaluación de activadores de microbiota de suelos, sobre rendimiento del cultivo de maíz duro (Zea mays L.), en la zona de Puebloviejo Provincia de Los Ríos - León Obando, José Gregorio (2018)
VIII. SUMMARY The cultivation of corn (Zea mays) it is a vegetable species that is part of the group of the gramineous ones more sowed worldwide after the wheat and the rice. The geographical distribution of the production of hard corn in the Costa concentrates 80% of the surface (Los Ríos 40%, Manabí 18% and Guayas 19% and 3% between Emeralds and El Oro); in the Sierra 17%, located basically in Loja and Bolívar; in the Amazonía 3%. The objective of this research is to evaluate the activators of microbiota in corn, to evaluate its effect on the yield. Treasury the Freedom. Located in the km 4,5 in the road Puebloviejo-Catarama. The hybrid ADV 9313 was investigated, with ten treatments and three repetitions, in parcels of 12 m2 that were distributed at random in a design of complete blocks. For the evaluation of stockings the test was used from Tukey to 5% of probability. During the cycle of the cultivation they were evaluated: height of plants, ear diameter, number of ears for plant, ear longitude, radical biomass, days to crop, days to flowering, weight seed, yield for hectare and an economic analysis and population of microorganisms. The results established that the application of Germinox impacts substantially on the development and production of the cultivation. The biggest yield was presented in the plants tried with Germinox in dose of 3,0 L/ha (10850,33 kg/ha), 4,5 L/ha (10684,0 kg/ha) and 6,0 L/ha (10589,0 kg/ha).